ANALYSIS PILE SLAB ON SWAMPLAND KATARAJA TOLL ROAD PROJECT - Rifqi Nadhif Qoid Mudhoffar; Gotot Slamet Mulyono (SEAN Institute, 2023)
Kataraja Toll Road has a length of 38.6 km and is a road infrastructure built due to government budget constraints. Because of these limitations, a mechanism for government cooperation with business entities is used. The construction of the Kataraja toll road is considered as one of the means of economic development policy and regional development. However, in its construction there was a problem in the road trase that had to cross the area with swampland. Marshland has a low soil carrying capacity. To solve the problem, roads were created with the Pileslab structure. In the Pileslab structure consists of pile heads, slabs, and pile foundations. The loading standard uses SNI T-02-2005, the bridge’s loading standard. Analysis using static methods and using the Allpile program. Based on the analysis conducted, it can be seen that pilelab can withstand vertical loads of 3300.89 kN and horizontal loads of 496.5 kN with eccentricities of up to 3 m. After analysis using the static method and the Allpile program, a decrease of 0.75332 cm and a deviation of 2.5 cm were obtained